Deficits in Agency in Schizophrenia, and Additional Deficits in Body Image, Body Schema, and Internal Timing, in Passivity Symptoms - Graham, Kyran T.; Martin-Iverson, Mathew T.; Holmes, Nicholas P.; Jablensky, Assen; Waters, Flavie (Frontiers in Psychiatry, 2014)
Individuals with schizophrenia, particularly those with passivity symptoms, may not feel in control of their actions, believing them to be controlled by external agents. Cognitive operations that contribute to these symptoms may include abnormal processing in agency, as well as body representations that deal with body schema and body image. However, these operations in schizophrenia are not fully understood, and the questions of general versus specific deficits in individuals with different symptom profiles remain unanswered. Using the projected hand illusion (a digital video version of the rubber hand illusion) with syn-chronous and asynchronous stroking (500 ms delay), and a hand laterality judgment task, we assessed sense of agency, body image and body schema in 53 people with clinically stable schizophrenia (with a current, past, and no history of passivity symptoms) and 48 healthy controls. The results revealed a stable trait in schizophrenia with no difference be-tween clinical subgroups (sense of agency), and some quantitative (specific) differences de-pending on the passivity symptom profile (body image and body schema). Specifically, a reduced sense of self-agency was a common feature of all clinical subgroups. However, subgroup comparisons showed that individuals with passivity symptoms (both current and past) had significantly greater deficits on tasks assessing body image and body schema, relative to the other groups. In addition, patients with current passivity symptoms failed to demonstrate the normal reduction in body illusion typically seen with a 500 ms delay in visual feedback (asynchronous condition), suggesting internal timing problems. Altogether, the results underscore self-abnormalities in schizophrenia, provide evidence for both trait abnormalities and state changes specific to passivity symptoms, and point to a role for internal timing deficits as a mechanistic explanation for external cues becoming a possible source of self-body input.